F-box protein FBXO32 ubiquitinates and stabilizes D-type cyclins to drive cancer progression - Feng Li; Hongqiang Yu; Yujun Zhang; Yuanhang Ma; Xinlei Chen; Jie Zhang; Liangbo Sun; Rui Guo; Ying Wu; Ping Zheng; Xiaojun Wang; Ping Bie; et al. (Nature Communications)
Abstract D-type cyclins (hereafter, cyclin D) are central regulators orchestrating G1/S cell cycle transition. Accordingly, aberrant expression of cyclin D is strongly correlated with proliferation-related diseases such as cancer. However, the mechanisms regulating cyclin D turnover are incompletely elucidated. Here we identify FBXO32, namely atrogin-1, as the E3 ubiquitin ligase that targets all three cyclin D for ubiquitination and stabilization. Specifically, FBXO32 catalyzes the lysine (Lys/K)27-linked polyubiquitination of cyclin D1 at the K58 site and subsequent stabilization. Moreover, GSK-3β inactivation-mediated dephosphorylation of cyclin D1 facilitates its interaction with FBXO32 and subsequent ubiquitination. Furthermore, FBXO32 exhibits tumor-promoting effect in mouse models and increased FBXO32 is associated with poor prognosis of cancer patients. Additionally, disrupting the FBXO32-cyclin D axis enhances the tumor-killing effect of cyclin-dependent kinase (CDK)4/6 inhibitor palbociclib. Collectively, these findings reveal that FBXO32 enhances the protein stability of cyclin D via K27-linked ubiquitination, and contributes to cancer progression and the limited response of cancer cells to CDK4/6 inhibitors.